An empirical evaluation of a model-based software testing tool - Villalobos Arias, Leonardo 1994-; Quesada López, Cristian Ulises 1979- (San José, Costa Rica, 2018)
Software testing is an essential part of software engineering, as it aims to deliver high quality software products to customers. Traditional software testing approaches have several limitations, such as the large amount of work required to manually design and execute test cases, and to automatically maintain the traceability between test cases and requirements. The model-based testing (MBT) approach addresses these limitations by automating test case design. This approach has been shown to find as many errors as manual testing, to generate high quality test cases, and to ensure com- pliance with coverage criteria. Several MBT techniques and tools have been proposed in the literature, but there is a lack of empirical evaluations that provide evidence of their actual benefits and limitations. This research brings evidence on the efficacy of an existing MBT tool, by per- forming an empirical evaluation. The main objective of our study is to characterize model-based testing tools and evaluate one of them based on its efficacy at finding errors and providing coverage. To achieve this we propose (1) to characterize model-based testing tools reported in the literature with respect to their support for MBT stages, (2) to assess these tools and select one of them for evaluation, and (3) to empirically evaluate its efficacy in error detection and coverage. We found 98 different MBT tools and characterized them in terms of their support for the stages of the MBT process: model specification, test selection criteria, test case generation, test case concretization, and test case execution. A total of 28 MBT tools were identified as being sufficiently supportive of the MBT process, and 6 of these support the entire MBT process. Additionally, we identified challenges and limitations of MBT tools and approaches. We selected a candidate tool (ModeUUnit) for our study evaluation, based...
Tesis (licenciatura en computación e informática)--Universidad de Costa Rica. Facultad de Ingeniería. Escuela de Ciencias de la Computación e Informática, 2018
Keywords: INGENIERIA DE PROGRAMAS PARA COMPUTADORA -- PRUEBAS; PROGRAMAS PARA COMPUTADORA -- PRUEBAS -- AUTOMATIZACION; PROGRAMAS PARA COMPUTADORA -- MODELOS DE EVALUACION; PROGRAMAS PARA COMPUTADORA -- EVALUACION